Multimodal Magnetic Resonance Imaging and Therapeutic Intervention With Yi-nao-jie-yu Decoction in a Rat Model of Post-stroke Depression - Zhao, Zijun; Zhang, Wen; Zhang, Yuan; Zhao, Yun; Zheng, Chunxiang; Tian, Huiling; Lei, Jianfeng; Liu, Yan; Zhao, Ruizhen; Tang, Qisheng (Frontiers in Psychiatry, 2020)
Post-stroke depression (PSD) is the most common neuropsychiatric complication after a stroke, though its neuropathological characteristics have not been fully elucidated. Comprehensive and noninvasive magnetic resonance (MR) assessment techniques are urgently needed for current research, as diffusion tensor imaging (DTI), arterial spin labeling (ASL), and magnetic resonance spectroscopy (MRS) can allow for a comprehensive assessment of neuropathological changes in the brain. These techniques can provide information about microscopic tissue integrity, cerebral perfusion, and cerebral metabolism, and can serve as powerful tools for investigating neurophysiological changes associated with PSD. Yi-nao-jie-yu decoction (YNJYD) is a Chinese herbal formulation based on the theory of traditional Chinese medicine (TCM), with demonstrated clinical efficacy in the treatment of PSD. The aim of this study was to use these MR techniques to evaluate changes in PSD and YNJYD-treated rats. This is the first experimental study in animals to investigate neuropathological changes associated with PSD using a combination of multiple MR techniques, including DTI, ASL, and MRS. In addition, we investigated the effect of YNJYD in a rat model of PSD by assessing changes in brain tissue microstructure, brain metabolism, and cerebral perfusion. First, depressive-like behaviors of PSD rats were assessed by the open field test (OFT), sucrose preference test (SPT), and Morris water maze (MWM) test, then the integrity of the rats’ microstructure was assessed by DTI, the levels of regional cerebral perfusion were assessed by ASL, and changes in the relative concentrations of brain metabolites were determined by MRS. The results showed that OFT and SPT scores were significantly reduced in PSD rats, as was performance in the MWM; these PSD-associated changes were attenuated in rats administered YNJYD, with improved depressive-like behaviors evidenced by increased OFT and SPT scores, and improved performance in the MWM task. Furthermore, we found that PSD rats had lower perfusion levels in the prefrontal cortex (PFC) and hippocampus (HP), microstructural damage, and abnormal changes in the concentrations of brain metabolites; YNJYD exerted therapeutic effects on PSD rats by improving microcirculation in the PFC and HP, regulating glutamatergic systems and membrane phospholipid metabolism, and repairing microstructural damage.